2016
DOI: 10.1590/s1806-37562016000000030
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive pattern on spirometry: association with cardiovascular risk and level of physical activity in asymptomatic adults

Abstract: Objective: To determine whether a restrictive pattern on spirometry is associated with the level of physical activity in daily life (PADL), as well as with cardiovascular disease (CVD) risk factors, in asymptomatic adults. Methods: A total of 374 participants (mean age, 41 ± 14 years) underwent spirometry, which included the determination of FVC and FEV1. A restrictive pattern on spirometry was defined as an FEV1/FVC ratio > 0.7 and an FVC < 80% of the predicted value. After conducting demographic, anthropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
(75 reference statements)
1
15
0
Order By: Relevance
“…Our finding that physical activity levels are lower among those with a restrictive spirometry pattern agrees with a previous report which was based on a small number (37) of cases. This previous work found a positive association between having a restrictive spirometry pattern and physical inactivity measured by accelerometer [32]. Cross-sectional studies have also identified that other constructs related to Odds ratios (OR) and 95% confidence interval for low physical activity in subjects with a restrictive spirometry pattern compared to those with a normal spirometry pattern (reference group), in ECRHS (dashed line), SAPA-LDIA (dotted line) and the meta-analysis (solid line).…”
Section: Main Findingsmentioning
confidence: 81%
“…Our finding that physical activity levels are lower among those with a restrictive spirometry pattern agrees with a previous report which was based on a small number (37) of cases. This previous work found a positive association between having a restrictive spirometry pattern and physical inactivity measured by accelerometer [32]. Cross-sectional studies have also identified that other constructs related to Odds ratios (OR) and 95% confidence interval for low physical activity in subjects with a restrictive spirometry pattern compared to those with a normal spirometry pattern (reference group), in ECRHS (dashed line), SAPA-LDIA (dotted line) and the meta-analysis (solid line).…”
Section: Main Findingsmentioning
confidence: 81%
“…Age and sex were selected as independent variables because they were well-known parameters which could affect the cardiac function. Meanwhile, FEV1.0% and %FVC were selected as independent variables because they were important parameters on spirometry that could clearly indicate respiratory condition [22]. Beta coefficients were interpreted as the absolute change in dependent variables per change in the pack-years intensity.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a cross-sectional study with participants selected from the Epidemiological Study of Human Movement (EPIMOV Study). Brie y, the EPIMOV Study is an epidemiological cohort study with the main purpose of investigate the longitudinal association between SB and physical inactivity and development of hypokinetic chronic diseases [16,17]. Exclusion criteria for the EPIMOV study were: regular use of gaiters and/or di culty performing physical exertion due to osteoarticular problems, recent respiratory infections, unstable or stable angina in the last four weeks, recent myocardial infarction, angioplasty or cardiac surgery in the last three months.…”
Section: Methodsmentioning
confidence: 99%